Stable representation of a naturalistic movie emerges from episodic activity with gain variability - Xia, Ji; Marks, Tyler D.; Goard, Michael J.; Wessel, Ralf (Nature communications, 2021)
Visual cortical responses are known to be highly variable across trials within an experimental session. However, the long-term stability of visual cortical responses is poorly understood. Here using chronic imaging of V1 in mice we show that neural responses to repeated natural movie clips are unstable across weeks. Individual neuronal responses consist of sparse episodic activity which are stable in time but unstable in gain across weeks. Further, we find that the individual episode, instead of neuron, serves as the basic unit of the week-to-week fluctuation. To investigate how population activity encodes the stimulus, we extract a stable one-dimensional representation of the time in the natural movie, using an unsupervised method. Most week-to-week fluctuation is perpendicular to the stimulus encoding direction, thus leaving the stimulus representation largely unaffected. We propose that precise episodic activity with coordinated gain changes are keys to maintain a stable stimulus representation in V1. Here the authors show that individual neural responses in mouse V1 to a repeated natural movie clip consist of episodic activity which is unstable in gain across weeks. Despite of the gain variability, time in the natural movie is stably represented by population activity in V1.